QGIS Shoreline Change Analysis Tool (QSCAT): A fast, open-source shoreline change analysis plugin for QGIS - Facun, Louis Philippe; Sta Maria, Ma. Yvainne; Ducao, Rodel; Clemente, Jamela Jirah; Carmelo, Ellen Mae; Maon, Angelo; Malaya, Ara Rivina; Cuison, Floribeth; Siringan, Fernando (Environmental modelling & software : with environment data news, 2025)
Coastal erosion poses a significant threat to most coastal communities. This necessitates a better understanding of coastal erosion dynamics, and thus, shoreline change analysis (SCA) tools would be handy. However, many available tools require commercial softwares and/or a faster computing platform. To address these issues, QGIS’ Shoreline Change Analysis Tool (QSCAT), a new QGIS plugin built with Python, was developed. QSCAT can perform transect-based and area-based analyses. The transect-based algorithm of QSCAT was patterned after the Digital Shoreline Analysis System (DSAS). Whereas, the area-based algorithm is similar to the change polygon method. Running QSCAT and DSAS together demonstrated that QSCAT generated the same results as DSAS but its overall speed is 8 times faster than DSAS. QSCAT can estimate beach area loss and length of eroding shorelines, which can identify erosion hotspots. These features attest to QSCAT’s potential as a more efficient and an equally reliable SCA tool. •For SCA, QSCAT is an equally reliable but relatively faster alternative to DSAS.•QSCAT can perform both transect-based and area-based analyses.•Development as a QGIS plugin enhances accessibility and adoption of QSCAT.